2022
DOI: 10.1007/s00253-022-12193-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth of antimicrobial resistance: the role of agriculture in the problem and the solutions

Abstract: The control of infectious diseases has always been a top medical priority. For years during the so-called antibiotic era, we enjoyed prolonged life expectancy and the benefits of superior pathogen control. The devastating failure of the medical system, agriculture and pharmaceutical companies and the general population to appreciate and safeguard these benefits is now leading us into a grim post-antibiotic era. Antimicrobial resistance (AMR) refers to microorganisms becoming resistant to antibiotics that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…There is an urgent need to develop new antibiotics and strategies to prevent the development of antibiotic resistance [77]. It is not only clinical environments that support the spread of ARGs, but wastewater treatment plants (WWTPs) and agriculture are also considered hotspots for ARG propagation [78][79][80][81]. If ARGs are not completely removed by wastewater treatment, they are released into the wastewater effluent.…”
Section: Biofilms As Reservoir For Antibiotic Resistance Genesmentioning
confidence: 99%
“…There is an urgent need to develop new antibiotics and strategies to prevent the development of antibiotic resistance [77]. It is not only clinical environments that support the spread of ARGs, but wastewater treatment plants (WWTPs) and agriculture are also considered hotspots for ARG propagation [78][79][80][81]. If ARGs are not completely removed by wastewater treatment, they are released into the wastewater effluent.…”
Section: Biofilms As Reservoir For Antibiotic Resistance Genesmentioning
confidence: 99%
“…Inhibition of the phc QS system is an attractive approach to control the pathogenicity and virulence of RSSC strains. Particularly, the pesticides that exert strong survival selection pressure on microbes, such as antibiotics and fungicides, will be increasingly difficult to use in the field (14,55,82). In studies of the AHL-QS systems, enzymatic degradation of signaling molecules was shown to dramatically affect bacterial virulence (22,23,32).…”
Section: Control Of the Phc Quorum-sensing System To Attenuate Virulencementioning
confidence: 99%
“…AMR studies from all over the world have reported widespread presence of resistance genes in water, soil as well as in food items. [143][144][145] This 'One health' approach of study underlines the importance of tracking resistance across abiotic environments alongside the clinics. 30 We thus looked for studies that reported whole-genome sequences of priority pathogens isolated from environments or food items.…”
Section: Indiamentioning
confidence: 99%